Effect of combination therapy with ceftizoxime and clotrimazole in the treatment of otomycosis - Saeid Mahdavi Omran; Zahra Yousefzade; Soraya Khafri; Mojtaba Taghizade Armaki; Keyvan Kiakojuri (Mazandaran University of Medical Sciences, 2018)
Background and Purpose: There are controversial findings regarding the efficacy of antifungal drugs in the treatment of a ruptured eardrum following fungal infections. Regarding this, the aim of the present study was to evaluate the therapeutic effect of the co-administration of antifungal and antibacterial agents in the treatment of otomycosis with tympanic membrane perforation. Materials and Methods: This analytical, clinical trial was conducted on 87 patients with otomycosis showing no bacterial elements in the direct observation and culture. The study population was assigned into two groups of intervention (n=45) and control (n=42). The demographic and clinical data, as well as the data related to the direct observation and culture of the ear samples were recorded in a checklist. All statistical analysis was performed in SPSS (version 24). Results: The most prevalent symptoms in both groups were hearing loss and itching, and the most common finding was secretion. Aspergillus and Candida were the most frequent fungi isolated from the samples. After the implementation of combination therapy, the intervention group demonstrated a significant decrease in symptoms and signs, compared to the control group (P=0.005). Conclusion: The findings of the present study indicated that the use combination therapy with ceftizoxime powder and clotrimazole ointment was effective the in treatment of the patients with tympanic membrane rupture showing no bacterial effects in direct examination and culture.